The INTERACT Trial: Long-term results of a randomised trial on preoperative capecitabine-based radiochemotherapy intensified by concomitant boost or oxaliplatin, for cT2 (distal)–cT3 rectal cancer. (May 2019) - Valentini, Vincenzo; Gambacorta, Maria Antonietta; Cellini, Francesco; Aristei, Cynthia; Coco, Claudio; Barbaro, Brunella; Alfieri, Sergio; D'Ugo, Domenico; Persiani, Roberto; Deodato, Francesco; Crucitti, Antonio; Lupattelli, Marco; et al.
Highlights: First available report on randomized study about intensification of radiochemotherapy by either radiotherapy dose escalation or multidrug chemosensibilisation, for Low-located cT2N0–2M0, cT3N0–2M0 (up to 12 cm from anal verge). Major pathological response rates (i.e.: TRG 1-2) were significantly improved in the RT dose escalated arm (Xelac arm 61.7% vs. Xelox 52.3%). Pathological complete response rates (primary outcome) did not differ between 2 arms. Xelox arm (multidrug chemosensibilisation) presented higher G ≥ 3 haematologic, upper gastrointestinal and neurologic toxicity. Patients achieving both major and pathological complete response presented significantly better clinical outcome (disease free and overall survival) irrespective of the treatment arm. Abstract: Background and purpose: Capecitabine-based radiochemotherapy (cbRCT) is standard for preoperative long-course radiochemotherapy of locally advanced rectal cancer. This prospective, parallel-group, randomised controlled trial investigated two intensification regimens. cT4 lesions were excluded. Primary objective: pathological outcome (TRG 1-2) among arms. Materials and methods: Low-located cT2N0–2M0, cT3N0–2M0 (up to 12 cm from anal verge) presentations were treated with cbRCT randomly intensified by either radiotherapy boost (Xelac arm) or multidrug concomitant chemotherapy (Xelox arm). Xelac: concomitant boost to bulky site (45 Gy/1.8 Gy/die, 5 sessions/week to the pelvis, +10 Gy at 1 Gy twice/week to the bulky) plus concurrent capecitabine (1650 mg/mq/die). Xelox: 45 Gy to the pelvis + 5.4 Gy/1.8 Gy/die, 5 sessions/week to the bulky site + concurrent capecitabine (1300 mg/mq/die) and oxaliplatin (130 mg/mq on days 1, 19, 38). Surgery was planned 7–9 weeks after radiochemotherapy. Results: From June 2005 to September 2013, 534 patients were analysed: 280 in Xelac, 254 in Xelox arm. Xelox arm presented higher G ≥ 3 haematologic ( p = 0.01) and neurologic toxicity ( p < 0.001). Overall, 98.5% patients received curative surgery. The tumour regression grade distribution did not differ between arms ( p = 0.102). TRG 1+2 rate significantly differed: Xelac arm 61.7% vs. Xelox 52.3% ( p = 0.039). Pathological complete response (ypT0N0) rates were 24.4 and 23.8%, respectively ( p non-significant). Median follow-up:5.62 years. Five-year disease-free survival rate were 74.7% (Xelac) and 73.8% (Xelox), respectively ( p = 0.444). Five-year overall survival rate were 80.4% (Xelac) and 85.5% (Xelox), respectively ( p = 0.155). Conclusion: Xelac arm significantly obtained higher TRG1-2 rates. No differences were found about clinical outcome. Because of efficacy on TRG, inferior toxicity and good compliance, Xelac schedules or similar radiotherapy dose intensification schemes could be considered as reference treatments for cT3 lesions.